Penyusunan Pesan Komunikasi Pendidikan Pada Masa Pandemi Covid-19 - Solehudin, Aden Hasan; Zakiah, Kiki; Chaerowati, Dede Lilis (Peneliti.net, 2024)
The study was entihed the creation of educational communication message in covid-19 pandemic (a case study of SMA Negeri 1 Wanayasa Purwakarta) The covid-19 pandemic has affected various sectors of humman life, one of which is education the message (teach materials) has on important role to contribute to the success of the online learning process, so the message must be as interesting as possible in order for the purposes of learning to be property accomplished. A teacher needs to pay attention at the media to use as a text message. The harmony of the message’s use of media is important to a teacher’s attention the purpose of the study is to know the creation of educational communications message during the covid-19 pandemic to analyze the relevant media used to communicate communications, education during the covid-19 pandemic and to explain the inportance of the deploymentof educational communication message during the covid-19 pandemic. The method use in this study are qualitative methods with case studies, using constructive paradigms, and using tee drafts of message Alan H Monroe and Cassandra. The object of this study is the process of creating educational communication message, the research subject is teachers who are capable of math, physics, chemistry, and students, selection of informants uses a purposive sampling technigue, data collection involves interviews, documenting, and literature studies whereas the chek of validity of data by triangulation source. The study suggests that the compilation of message by teacher begins with attracting students first, the listens to the reasons of why students need the teacher can convince students to the study the material being presented, the role of coming message communication has a particulary important to make it easier for teacher to deliver learning message, improve the quality of learning make it easier for teacher to determine learning strategies the communication media use online learning activities ia audio visual media (zoom meeting, google meet, google classroom) and text based media (whatsapp) there are the differences a form of communication message arranged online is compared to the offline of learning message